Community-based health care providers as research participant recruitment gatekeepers: ethical and legal issues in a real-world case example. (April 2021) - Celedonia, Karen L; Valenti, Michael W; Corrales Compagnucci, Marcelo; Lowery Wilson, Michael
Community-based mental health care providers (CBMHCPs) are increasingly contacted by external researchers for research study recruitment. Unfortunately, many do not possess the resources or personnel with the skills required to successfully evaluate research proposals for risks. Providing access to clients and client health information can result in harmful personal and legal consequences if the proper safeguards do not exist. This article discusses the legal requirements and practical implications for CBMHCPs when acting as gatekeepers. A case study from a large CBMHCP is presented as an illustration of steps that can be taken to protect clients and avoid risk. Additional recommendations for establishing protective safeguards and research evaluation protocols are discussed.